Izbrane tematske poti v LAS Srce Slovenije in GIS aplikacija - Hauptman, Barbara (Geografski obzornik, 2023)
Thematic trails are experiential hiking trails that educate the visitor about a particular topic through recreation. We analysed seven thematic trails in the area of the Local action group »Srce Slovenije«. We obtained available literature and information, carried out field analyses, developed a geoinformation application and made proposals for their management. We found that there are various shortcomings and, depending on the type of thematic trail, we propose activities to upgrade the supporting infrastructure, also from the perspective of the local community needs.
Keywords: geografski informacijski sistemi; izobraževanje; local action group; podeželje; recreation; rekreacija; rural areas; Slovenia; Slovenija; tematske poti; thematic trails; turistična geografija; web geoinformation application